THE REAL WOMAN: BEAUTIFUL, EMPODERATED AND READER - Paula, Luciane de [UNESP]; Sant'ana, Carolina Gomes [UNESP] (Univ Fed Goias, Campus Catalao, 2020)
This article aims to analyze the cover and an article from the magazine O Diabo a Quatro, from 1879, as an answer to movements that fought for the inclusion of women in politics, in comparison with the article Bela, recatada e 'do lar', from the magazine Veja, from 2016; and with statements from members (officials or not) from Bolsonaro's government (Damares Alves, minister of Women, Family and Human Rights; and Italo Marsili, doctor suggested to be minister of Health) about women, her rights and duties. The theoretical-methodological foundation is based on the concepts of ideology, dialogue and social voices from Balchtinian studies. The results reveal how much, at any time, if, on the one hand, the feminist movements act with full force, on the other, with the same strength, traditional movements that reproduce conservative values answer actively. Reflecting about this clash of social forces is the relevance of this text.
Keywords: Balchtinian studies; Dialogue; Ideology; Social voice; Woman